Protocol to Induce the Temporary Opening of the Blood–Brain Barrier with Short-Time Focused Ultrasound in Rats - Jorge A. Rodríguez; Mario I. Gutiérrez; Arturo Vera; Daniel A. Hernández; Juan M. Gutiérrez; Daniel Martínez-Fong; Lorenzo Leija (Pharmaceutics, 2023)
Brain neurodegenerative diseases are central nervous system (CNS) affections typically common in older adults. A new therapeutic approach for them consists of providing specific drugs to the CNS through blood circulation; however, the Blood–Brain Barrier (BBB) prevents almost 100% of neurotherapeutics from reaching the brain. There are indications that Focused Ultrasound (FUS), temporarily placed in the BBB, can achieve a controlled increase in temperature at its focus, allowing temporary, localized, and reversible opening of this barrier, which facilitates the temporary delivery of specific drugs. This work presents a FUS-based protocol for the local, temporary, and reversible opening of the BBB in Wistar rats. The proposed protocol specifies certain power, treatment times, and duty cycle to controllably increase the temperature at the region of interest, i.e., the substantia nigra. Numerical simulations using commercial software based on the finite element method were carried out to determine the optimal size of the craniotomies for nearly full-acoustic transmission. Experiments in rats were performed with the parameters used during computational simulations to determine the adequate opening of the BBB. For this, craniotomies of different sizes were made at coordinates of the substantia nigra, and FUS was applied from the exterior. The opening of the BBB was evaluated using Evans Blue (EB) as an indicator of the crossing of the dye from the blood vessels to brain tissue. Numerical simulations demonstrated a major distance reached by the ultrasound focus with a bigger diameter. Experimental results show the local, temporary, and reversible opening of the BBB through a 10 mm diameter craniotomy, which effectively allowed placing the ultrasound focus over the substantia nigra, unlike a 6 mm diameter craniotomy in which there is a deviation of the focus through that window. Moreover, from these results, it was also determined that the disruption of the BBB was reversible, with an opening duration of 6 h after FUS application. The experimental work developed in this study resulted in a minimally invasive method for the temporary opening of the BBB.